Business Feasibility Study: Consulting Services and Legal Assistance (Case Study on Bilik Hukum) - Agus Angling Kusumah; Frischa Sonawaty Theresia Sianturi; Rhian Indradewa; Semerdanta Pusaka; Agus Munandar (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the feasibility of the legal advisory and legal assistance service